Avaliação de variáveis operacionais e aplicação de enfoque híbrido na modelagem do processo de produção de penicilina G acilase por Bacillus megaterium - Tonin, Fábio Cristiano (2005)
In the present work it was studied the influence of operational conditions particularly dissolved oxygen concentration in the penicillin G acylase (PGA) production. The experiments were carried out in aerated and agitated bioreactor employing bacteria Bacillus megaterium. The production of PGA is sensitive to dissolved oxygen concentration during its cultivation. As much its lack as its excess can be reduces PGA production. As regarding dissolved oxygen concentration the experiments realized in 10% of its saturation showed the better results. The media composition was not significantly influence on enzyme production. The use of potassium acetate instead of phenyl acetic acid as well as the reduction of eighteen for seven amino acids did not have effect on the cells and enzyme concentrations obtained. It was proposed an hybrid model combining mass balance equation with artificial neural network to infer the cellular concentration during the process. The proposed model showed good results to modeling cellular concentration in both training and validate data sets.